Nrf2 Overexpression Decreases Vincristine Chemotherapy Sensitivity Through the PI3K-AKT Pathway in Adult B-Cell Acute Lymphoblastic Leukemia - Wang, Li; Liu, Xin; Kang, Qian; Pan, Chengyun; Zhang, Tianzhuo; Feng, Cheng; Chen, Lu; Wei, Sixi; Wang, Jishi (Frontiers in Oncology, 2022)
Uncontrolled proliferation is an important cancer cell biomarker, which plays a critical role in carcinogenesis, progression and development of resistance to chemotherapy. An improved understanding of novel genes modulating cancer cell proliferation and mechanism will help develop new therapeutic strategies. The nuclear factor erythroid 2-related factor 2 (Nrf2), a transcription factor, decreases apoptosis when its expression is upregulated. However, the relationship between Nrf2 and Vincristine (VCR) chemotherapy resistance in B-cell acute lymphoblastic leukemia (B-ALL) is not yet established. Our results showed that Nrf2 levels could sufficiently modulate the sensitivity of B-ALL cells to VCRby regulating an apoptotic protein, i.e., the Bcl-2 agonist of cell death (BAD). Chemotherapeutic agents used for the treatment of B-ALL induced Nrf2 overactivation and PI3K-AKT pathway activation in the cells, independent of the resistance to chemotherapy; thus, a potential resistance loop during treatment for B-ALL with a drug combination is established. Therefore, B-ALL patients with a high expression of Nrf2 might mean induction chemotherapy with VCR effective little.